In Vitro Sensitivity Test of Escherichia coli ATCC 25922 to Various Antibiotics with Well Diffusion Method - Eliya Mursyida; Olvaria Misfa; Sasa Billa Pratiwi; Akhilesh Shinde (poltekkes kemenkes mataram, 2023)
Escherichia coli ATCC 25922 is an opportunistic normal flora bacteria that can cause diseases such as diarrhea and other intestinal tract diseases. Acute diarrhea is the discharge of loose/liquid stools with a frequency of more than 3 times a day or more lasting less than 14 days. Until now acute diarrheal infections are caused by Escherichia coli usually treated with antibiotics. However, it is known that there is resistance of Escherichia coli bacteria to several antibiotics such as ampicillin, tetracycline, sulfamethoxazole-trimethoprim, cotrimoxazole, chloramphenicol, ciprofloxacin, and gentamicin caused by controlled use of antibiotics. This study aims to analyze the sensitivity of various antibiotics to Escherichia coli ATCC 25922 bacteria in vitro. This research is an experimental study with a post-test only with control group research design and uses various antibiotics as samples. The test bacteria used in this study was Escherichia coli ATCC 25922, with the agar diffusion method (well). The diameter of the inhibition zone formed was measured using a caliper. The results of the sensitivity test of various antibiotics against Escherichia coli were found to be 5 resistants, namely sulfamethoxazole-trimethoprim 1.25µg (8,90mm), cefotaxime 30µg (12,26mm), cefixime 30µg (5,20mm), ceftriaxone 30µg (10,66mm), chloramphenicol 30µg (8,80mm), 3 intermediates namely ampicillin 10µg (16,00mm), gentamicin 10µg (13,55mm), erythromycin 15µg (17,53mm), and 2 sensitives, namely tetracycline 30µg (25,80mm), ciprofloxacin 5µg (23,31mm).